Pengaruh Dukungan Sosial Terhadap Stres dan Kecemasan Pada Mahasiswa Prodi BPI UIN Syarif Hidayatullah Jakarta - Khoirunnisa, Qonitah Fitri; Andini, Kayla; N, Najarudin; Rahmayani, Putri Nur Azizah; Prihatini, Rini (Madani: Jurnal Ilmiah Multidisiplin, 2025)
During their academic years, students often face stress and anxiety, which commonly occur due to both internal and external pressures. Social support plays a crucial role in helping students emotionally and materially, providing trust, empathy, or care, as well as offering recognition, such as feeling valued and accepted. This study aims to determine the influence of social support on stress and anxiety among students. The research method used is a quantitative approach with purposive sampling, involving 58 respondents. Data analysis was conducted using the chi-square test, which showed no significant relationship between social support and stress or anxiety.